(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
Rickets is a skeletal disorder that primarily affects children, leading to weakened and deformed bones due to deficiencies in vitamin D, calcium, or phosphate. This article explores the specific aspects of rickets, including its causes, symptoms, diagnostic methods, treatment approaches, and prevention strategies. The condition can result from insufficient sunlight exposure, poor nutrition, genetic factors, or underlying medical conditions. The article also highlights the role of early diagnosis and proper management in preventing complications such as bone deformities, growth retardation, and fractures. Emphasis is placed on the importance of vitamin D supplementation, dietary adjustments, and lifestyle modifications to combat rickets effectively.